2009
DOI: 10.5194/angeo-27-2755-2009
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in satellite remote sensing of aerosols and impact on monitoring its long-term trend: a review and perspective

Abstract: Abstract. As a result of increasing attention paid to aerosols in climate studies, numerous global satellite aerosol products have been generated. Aerosol parameters and underlining physical processes are now incorporated in many general circulation models (GCMs) in order to account for their direct and indirect effects on the earth's climate, through their interactions with the energy and water cycles. There exists, however, an outstanding problem that these satellite products have substantial discrepancies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
233
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(235 citation statements)
references
References 112 publications
1
233
0
1
Order By: Relevance
“…(4) is a measure of the sensitivity of the algorithm to the assumed aerosol microphysical properties. This is an important factor affecting retrieval uncertainty (Li et al, 2009;Povey and Grainger, 2015), but, as mentioned in the introduction, there are many other sources of error not accounted for in this approach. Hence, the AOD uncertainty obtained from the algorithm should not be interpreted as a measure of how far the retrieved AOD deviates from the truth.…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
“…(4) is a measure of the sensitivity of the algorithm to the assumed aerosol microphysical properties. This is an important factor affecting retrieval uncertainty (Li et al, 2009;Povey and Grainger, 2015), but, as mentioned in the introduction, there are many other sources of error not accounted for in this approach. Hence, the AOD uncertainty obtained from the algorithm should not be interpreted as a measure of how far the retrieved AOD deviates from the truth.…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
“…The system provides aerosol optical depth, volume backscatter coefficient, cross section, and depolarization profiles with high temporal and vertical resolution (Eloranta 2005). These quantities can be used for example in identifying the dominant aerosol type for different layers using a combination of lidar ratio and depolarization (Li et al 2009, Petzold et al 2009). 15…”
Section: Ground-based Instrumentationmentioning
confidence: 99%
“…IPCC) the decadal variations of atmospheric aerosol loadings are gaining increased interest from both the scientific and policy community (e.g. Kishcha et al, 2007;Mishchenko et al, 2007aMishchenko et al, , 2009Remer et al, 2008;Zhao et al, 2008;Li et al, 2009a;Herman et al, 2009;Li et al, 2009b;Streets et al, 2009;Yu et al, 2009;Cermak et al, 2010). Such studies are plagued by calibration issues (both within and between multiple sensors), signal to noise issues, and the aforementioned retrieval biases (e.g., Zhang and Reid, 2006;Li et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Kishcha et al, 2007;Mishchenko et al, 2007aMishchenko et al, , 2009Remer et al, 2008;Zhao et al, 2008;Li et al, 2009a;Herman et al, 2009;Li et al, 2009b;Streets et al, 2009;Yu et al, 2009;Cermak et al, 2010). Such studies are plagued by calibration issues (both within and between multiple sensors), signal to noise issues, and the aforementioned retrieval biases (e.g., Zhang and Reid, 2006;Li et al, 2009b). For example, using 23 years of Advanced Very High Resolution Radiometer (AVHRR) data, Mishchenko et al (2007b) studied the averaged aerosol optical depth (AOD) over global ocean and found a significant decreasing trend in AOD from 1991 to 2005 (GACP, Mishchenko et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%